Impact of Exposure to Benzo[b]fluoranthene and Aging on Mutations in Male Mouse Germ Cells - Stewart, Madison (Université d'Ottawa | University of Ottawa, 2025)
Mutations in germ cells accumulate with age and can lead to inherited disorders; thus, it is critical to identify the endogenous and exogenous factors that contribute to their formation. Polycyclic aromatic hydrocarbons (PAHs) are widespread combustion by-products that are ubiquitous in the environment. Long-term exposure to these harmful compounds can have serious implications to health. Benzo[b]fluoranthene (BbF) is a PAH that induces mutations in mouse somatic tissues and is classified as a possible human carcinogen. However, the effects of BbF on germ cells are unknown. Age-related spontaneous mutations in male germ cells are attributed to lower fertility and elevated risk of genetic disease in the offspring; making it necessary to deeply characterize the effects of aging on the male germline. We evaluated the effects of long-term BbF exposure and aging on male germ cells. Adult MutaMouse males were exposed orally to BbF dissolved in olive oil at doses of 0 (controls), 3.25, 6.25, 12.5, 25, or 50 mg/kg BW/day for 90 days or at 0, 1.5625, 3.125, 6.25, 12.5, or 25 mg/kg body weight per day (BW/day) for 180 days. Mutant frequencies were determined in germ cells from the seminiferous tubules using the lacZ assay (n = 8 per dose group). Control and high dose groups for each time point were then sequenced to detect mutations using Duplex Sequencing (DS; n = 6 per group). The effects of aging were investigated in unexposed male mice at 3, 13-15, 25-27, and 35-37 weeks of age. There were no significant effects of BbF at 90 or 180 days using either methodology. Similarly, there were no significant increases in C:G > A:T mutations, the major mutation induced by BbF in somatic tissues. Our power analysis based on observed variation and mutation frequencies shows that a larger sample size is required to detect an effect of BbF with 80% power relative to somatic tissues. We also did not observe an age-related increase in spontaneous mutation frequency using DS; however, a significant age-dependent increase in mutant frequency was detected using the lacZ assay, which may be explained by an unusually low mutant frequency at 13-15 weeks relative to the historical control database. There were no significant increases in C:G > T:A mutations, the predominant age-associated mutation expected, at 35-37 weeks relative to 3 weeks; however, there was a significant age-related trend in these mutations. Overall, lack of a BbF effect may be explained by high germline DNA repair capacity or by pharmacokinetic differences between somatic and germ cell tissues (e.g., distribution of BbF to the germ cells and metabolic activation). Our results also suggest that older animals may be required to detect an age-related effect on mutations in male mouse germ cells.
Keywords: Germ cells; Transgenic rodent gene mutation assay; LacZ assay; Duplex sequencing; Mutation frequency; Mutation spectrum